Kinetic model generation from triangular mesh models - Park, Ji M.; Ko, Min S.; Lee, Woong G.; Park, Sang C. (Computer-Aided Design and Applications, 2020)
The virtual commissioning technology has been considered as a very effective tool to detect and correct errors generated during the design stage of a production system. To enjoy the benefits of virtual commissioning technology, it is essential to develop a more efficient methodology to construct virtual device models. A virtual device model consists of two sub-models, a geometric model and a kinetic model. This paper proposes a methodology to extract a kinetic model from the geometric model of a virtual device. The proposed approach consists of four steps; 1) find all cylindrical shapes from two links, 2) identify sliding surface areas from the set of cylindrical shapes, 3) identify the limiting surface areas by finding the adjacent triangles of the sliding surface areas, and 4) identify a joint between two given links. Among the four steps, the first step, finding cylindrical shapes from a solid model, is not a trivial problem when the design history information is not available. To solve the problem, we devise the concept of a T-Gauss map. By using the T-Gauss map, we can easily find cylindrical shapes by finding great circles on a T-Gauss map. The proposed procedure has been implemented and tested with various examples.
Keywords: Cylindrical shapes; Gauss maps; Geometric modeling; Kinetic modeling; Production system; Triangular meshes; Virtual commissioning; Virtual device models; Fixture modeling; Gauss map; Geometric model; Kinetic model; Virtual commissioning